EVALUASI LAYANAN RESEP RAWAT JALAN DI INSTALASI FARMASI: WAKTU TUNGGU DAN KENDALA - Roselina, Elsa; Nurfikri, Ari; Aulia, Okta (UI Scholars Hub, 2021)
Waiting time for prescription services is one indicator of minimum pharmacy service standards. This study aims to determine the average time, coverage of compliance, and to find out the obstacles related to prescription services. This research uses mixed methods. The quantitative approach was carried out using the prescription service worksheet instrument. The qualitative approach was carried out by observing the process during the prescription service. Data were taken from March to April 2019 at a private type B hospital in West Java Province. The number of samples was determined based on the Slovin formula with an error tolerance value of 5%, obtained a sample of 60 non-concoction prescriptions and 60 concoction prescriptions. This study applied descriptive statistics with univariate analysis. The results showed the average service time for non-concoction prescriptions was 26 minutes 58 seconds and 40 minutes 14 seconds for concoction prescriptions. The coverage of the suitability of service time based on the Decree of the Minister of Health of the Republic of Indonesia was 68% (non- concoction prescriptions) and 92% (concoction prescriptions), while according to the hospital's internal quality standards it was 3% (non-mixed prescriptions) and 15% (concoction prescriptions). Several obstacles occurred during the process of receiving prescriptions, working on compound prescriptions, submitting prescriptions, confirming doctors, and peak days for patients. The establishment of hospital internal quality standards related to the timing of prescription services needs to be reviewed and the application of the lean hospital concept needs to be considered.